2008
DOI: 10.3989/gya.2008.v59.i3.511
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic characteristics of <i>Lactobacillus plantarum</i> strains from traditional butter made from camel milk in arid regions (Sahara) of Algeria

Abstract: RESUMENCaracterísticas probióticas de cepas de Lactobacillus plantarum de mantequilla tradicional de leche de camello de regiones áridas (Sáhara) de Argelia.Se evalúan algunas características probióticas de cepas de Lactobacillus plantarum aisladas de la mantequilla tradicional elaborada a partir de leche de camello (shmen). De 38 cepas investigadas para resistencia biliar, 14 fueron tolerantes a un 2% oxgall con porcentajes de supervivencia entre 69 y 75%. De éstas, sólo 4 cepas (L. plantarum SH5, SH12, SH24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Oh et al (2000) studied antimicrobial activity of proteinaceous compound produced by L. acidophilus 30SC strain, the bacteriocin was completely stable at pH 6 and 7and 50% of activity lost after adjusting to the various pH values between 3 and 10. Maurad and Meriem (2008) reported that the antimicrobial activity of L. plantarum isolated from camel milk butter was stable at pH 2-6 but the activity was lost at pH 8 against indicator strain of Lactococcus lactis B8. Ollveira et al (2008) isolated Lactobacillus casei GC subgroup A from vacuum packaged beef and had antagonistic activity against indicator strains of L. acidophilus, L. fermentum and L. plantarum; the activity was stable at pH 4-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oh et al (2000) studied antimicrobial activity of proteinaceous compound produced by L. acidophilus 30SC strain, the bacteriocin was completely stable at pH 6 and 7and 50% of activity lost after adjusting to the various pH values between 3 and 10. Maurad and Meriem (2008) reported that the antimicrobial activity of L. plantarum isolated from camel milk butter was stable at pH 2-6 but the activity was lost at pH 8 against indicator strain of Lactococcus lactis B8. Ollveira et al (2008) isolated Lactobacillus casei GC subgroup A from vacuum packaged beef and had antagonistic activity against indicator strains of L. acidophilus, L. fermentum and L. plantarum; the activity was stable at pH 4-9.…”
Section: Discussionmentioning
confidence: 99%
“…Coconnier et al (1997) isolated L. acidophilus strain LB from human was relatively sensitive to trypsin, proteinase Kand pronase and showed antimicrobial activity against K. pneumoniae, Enterobacter spp., S. Typhimurium, E.coli, L. monocytogenes, S. flexneri and P. aeruginosa. However, Maurad and Meriem (2008) reported that antibacterial activity of L. plantarum isolated from butter made from camel milk against indicator strain of Lactococcus lactis B8 was lost when treated with α-chymotrypsin and proteinase K.…”
Section: Discussionmentioning
confidence: 99%
“…This bacteriocin activity was similar to Thermophilin 110 Gilbreth and Somkuti (2005), Thermophilin A (Ward and Somkuti, 1995) Thermophilin T (Aktypis et al, 1998) and the bacteriocin of S. thermophilus 580 (Mathot et al, 2003) in this manner. The inactivation of the bacteriocin by treatments with lipase enzymes (Table 3) suggests that activity was dependent on the presence of either a carbohydrate or lipid moiety as described by Maurad and Meriem (2008).…”
Section: Sensitivity Of Bacteriocin To Ph Temperature and Enzymesmentioning
confidence: 99%
“…Lore et al (2005) (Quan et al, 2006). Maurad and Meriem (2008) isolated thirty-eight lactic acid bacteria (Lactobacillus plantarum-SH1 to SH38) from traditional butter which was prepared using Shmen (fermented camel milk) as a starter culture. Among these strains SH12 and SH24 showed promising probiotic potential, high acidifying rates, and proteolytic activity.…”
Section: Strains Of Lab Isolated In Different Fermented Camel Productsmentioning
confidence: 99%